Galanin Regulates Myocardial Mitochondrial ROS Homeostasis and Hypertrophic Remodeling Through GalR2 - Boal, Frederic; Cinato, Mathieu; Timotin, Andrei; Münzberg, Heike; Qualls-Creekmore, Emily; Kramar, Solomiia; Loi, Halyna; Roncalli, Jerome; Keita, Sokhna; Tronchere, Helene; Kunduzova, Oksana (Frontiers in Pharmacology, 2022)
The regulatory peptide galanin is broadly distributed in the central nervous systems and peripheral tissues where it modulates numerous physiological and pathological processes through binding to its three G-protein-coupled receptors, GalR1-3. However, the function and identity of the galaninergic system in the heart remain unclear. Therefore, we investigated the expression of the galanin receptors in cardiac cells and tissues and found that GalR2 is the dominant receptor subtype in adult mouse hearts, cardiomyocytes and H9C2 cardiomyoblasts. In vivo, genetic suppression of GalR2 promotes cardiac hypertrophy, fibrosis and mitochondrial oxidative stress in the heart. In vitro, GalR2 silencing by siRNA abolished the beneficial effects of galanin on cell hypertrophy and mitochondrial reactive oxygen species (ROS) production. These findings unravel new insights into the role of galaninergic system in the heart and suggest novel therapeutic strategies in heart disease.